Pengujian Aplikasi E-FARMER dalam Perhitungan Keuntungan dengan Metode Blackbox Testing Boundary Value Analysis - Desi Novianti; Dewi Anjani (Program Studi Teknik Informatika, Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
A software Testing is one of the stages in building an application where the test device that is implemented imperfectly certainly has a bad effect on the resulting software. E-farmer is an android based application that can provide a farmer experience to calculate the yield of profits for each harvest. The purpose of testing E-farmer is to see the error rate that occurs in the software. So that by testing this application, it is hoped that the application made is in accordance with the function and purpose of the application. Where this test uses the Black-box Testing method with the Boundary Value Analysis approach. The results obtained from this study are testing shows that the application has a success rate of 88, 89%. Three fields need to be improved, namely the id_petani, year, and semester fields.